Towards the Concurrent Optimization of the Server: A Case Study on Sport Health Simulation. (15th March 2021) - Jia, Nan; Wang, Ruomei; Li, Mingliang; Guan, Yuhan; Zhou, Fan
Abstract : Using computers to conduct human body simulation experiments (e.g., human sport simulation, human physiology simulation, and human clothing simulation) can benefit from both economic and security. However, the human simulation experiment usually requires vast computational resources due to the complex simulation model which combines complicated mathematical and physical principles. As a result, the simulation process is usually time-consuming and simulation efficiency is low. One solution to address the issue of simulation efficiency is to improve the computing performance of the server when the complexity of the simulation model is determined. In this paper, we proposed a concurrent optimization scheme for the server that runs simulation experiments. Specifically, we firstly propose the architecture of the server cluster for the human body simulation, and then we design the concurrent optimization scheme for the server cluster by using Nginx. The experiment results show that the proposed concurrent optimization scheme can make better use of server resources and improve the simulation efficiency in the case of human sport simulation.